High Fish Biomass and Low Nutrient Enrichment Synergistically Enhance Stability in a Seagrass Meta‐Ecosystem - Maximilian H. K. Hesselbarth; Jacob E. Allgeier (Conservation Letters)
ABSTRACT Tropical seagrass ecosystems are globally imperiled due to overfishing and anthropogenic disturbances. Sustaining the services they provide will require managing resilience, particularly with increased volatility from climate change. Portfolio theory is touted as a mechanism to increase resilience in ecosystems because it takes advantage of temporal volatility in local production dynamics to increase stability at larger spatial scales. Using an individual‐based model of a network of artificial reefs across multiple seagrass ecosystems that is parameterized with 15 years of field data, we demonstrate that (1) the large fish populations and the low enrichment synergistically increase portfolio effects; (2) the mechanism was via reduced local and increased meta‐ecosystem stability in primary production; and (3) stability was greatest under intermediate production because nutrient enrichment reduces and fish, which have less influence on the amount of production, promote stability. Integrating common‐sense management with portfolio theory can stabilize the services provided by seagrass ecosystems.